Pengembangan Handout Mikrobiologi Berbasis Hasil Penelitian Antagonisme Fungi Antagonis terhadap Fungi Patogen pada Tanaman Stroberi - Izzatinnisa’ Izzatinnisa’; Utami Sri Hastuti; Abdul Gofur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
The objectives of this study were: 1) to produce a Microbiology handout based on the results of the study of Antagonistic Fungi Antagonism against Pathogenic Fungi in Strawberry Plants; and 2) testing the feasibility and practicality of the handout. This type of research is development research. The development model used in this research is the ADDIE model which consists of 5 stages, namely: Analyze, Design, Develop, Implement, and Evaluate. The handout material was selected based on the results of the needs analysis by the respondent students of the Biology Study Program, FMIPA, State University of Malang. Handout eligibility data obtained from the results of validation by microbiology material experts and learning media experts. Meanwhile, the handout practicality data was obtained from the readability assessment results of Biology Study Program students who were currently taking the Microbiology course. The results showed that, the percentage of eligibility of handout material by the expert validator of microbiology material was 99.53% with very high or very valid eligibility criteria. The percentage of eligibility of handouts by instructional media expert validators is 98.14% with very high or very valid eligibility criteria. The percentage of practicality tests by students who were taking the Microbiology course resulted in 89.89% with very high practicality criteria. The results showed that research results-based Microbiology handouts were very feasible and practical to be used in microbiology learning activities.